Shenkang recipe alleviates renal aging in diabetic kidney disease by interfering with the lysine-specific demethylase KDM6B to modulate the PPAR-γ signaling pathway - Anna Zuo; Jiarun Xie; Junqiao Shao; Shuyu Li; Haoyu Lin; Shaoting Wang; Wei Sun; Jinjin Xia; Weiqiang Jiang; Jia Sun; Ming Wang (Elsevier, 2023)
Objective: Diabetic kidney diseases (DKD) is one of the most common and serious microvascular complications of diabetes, and is also a major cause of end-stage renal diseases and death in diabetic patients. Shenkang Recipe (SKR) is a traditional Chinese medicine formula that has been shown to be effective against DKD in clinical practice, however, its mechanism of action remains unclear. The study is to explore the anti-aging effects and potential molecular mechanisms of SKR in the renal aging process. Methods: The active ingredients of SKR were identified by UHPLC-MS/MS. A DKD mouse model was induced using unilateral nephrectomy combined with intraperitoneal injection of STZ (60 mg/kg), followed by gavage of SKR (14.18, 28.36, 56.72 g/kg/d, ig) for 12 weeks in DKD mice, Dagliflozin (5 mg/kg/d, ig) was used as a positive control. The renal pathological damage was observed by HE, PAS and Masson staining. The expression levels of aging-related biomarkers were measured by RT-qPCR and Western blot. In vitro experiments, D-galactose was used to induce senescence in HMC cells, and the molecular mechanisms involved in the improvement of senescence by SKR were explored through the administration of GSK-J1 and FH535. Results: It was found that SKR treatment significantly attenuated renal pathological damage, alleviated the renal aging process in DKD mice and inhibited the activation of histone demethylase KDM6B. Transcriptomic analysis suggested that the PPAR signaling pathway was identified to be most significantly changed in the kidneys of DKD mice, including PPAR-α, PPAR-β, and PPAR-γ. The pharmacological inhibition of KDM6B demethylase activity by GSK-J1 could alleviate D-galactose-induced senescence in HMC cells, but this effect could be reversed by FH535, an inhibitor of PPAR-γ. Conclusion: These results suggest that SKR plays a role in delaying the renal aging process in DKD mice by interfering KDM6B to promote the PPAR-γ signaling pathway.